2017
DOI: 10.24843/jaa.2017.v06.i01.p11
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Finansial Usaha Peternakan Babi (Studi Kasus Peternakan Babi UD Karang di Desa Jagapati, Kecamatan Abiansemal,Kabupaten Badung)

Abstract: Business Financial Analysis on Piggery (A Case Study of Piggery of UD Karang at Jagapati Village, Sub-District of Abiansemal, Badung)Pigs is one commodity of livestock meat producer. Pigs have qualities and abilitiesthat benefit namelyit hasfaster growth rate and also a higher number of piglets perbirth. Pork demand has improved in the area of Bali that can provide businessopportunities to UD Karang to develop a piggery by raising pigs to be fattening.Piggery business needs to do a financial analysis to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
1
2
Order By: Relevance
“…In the pig-finishing type, 76.48% of cash are also used to buy feed, especially factory feed (36.79%) and factory waste (39.69%), while in the nursery type, 81.66% of cash are allocated to buy feed, especially factory feed (34.61%) and factory waste (22.13%) as well as to pay labors (24.92%). The average cost of feed in this study was relatively higher when compared to the case study results of Kueain et al (2017) on a farm in Bali. Based on observations of the data series for six years, they found that the cost of feed was 63.80% of the total cost.…”
Section: Cash Structurecontrasting
confidence: 63%
“…In the pig-finishing type, 76.48% of cash are also used to buy feed, especially factory feed (36.79%) and factory waste (39.69%), while in the nursery type, 81.66% of cash are allocated to buy feed, especially factory feed (34.61%) and factory waste (22.13%) as well as to pay labors (24.92%). The average cost of feed in this study was relatively higher when compared to the case study results of Kueain et al (2017) on a farm in Bali. Based on observations of the data series for six years, they found that the cost of feed was 63.80% of the total cost.…”
Section: Cash Structurecontrasting
confidence: 63%
“…Ternak babi sangat potensial untuk dikembangkan, karena memiliki berbagai keunggulan, diantaranya efisien dalam mengkonsumsi pakan, sangat prolifik yakni beranak dua kali setahun (Manampiring S. P., 2020). Keuntungan dari beternak babi adalah selain sebagai penghasil daging, pakan untuk ternak babi mudah diperoleh (ternak babi tergolong dalam hewan omnivora) serta kotorannya berpotensi digunakan sebagai pupuk alami (Kueain et al, 2017).…”
Section: Latar Belakangunclassified
“…menegaskan bahwa pada usaha peternakan rakyat biasanya peternak berfungsi sebagai pembuat keputusan yang berusaha mengambil keputusan secara efektif dan efisien dalam menjalankan dan mengelola usahanya sehingga secara tidak langsung menyediakan lapangan usaha bagi rumah tangga masyarakat. Keuntungan lain dari beternak babi; selain sebagai penghasil daging, adalah makanan babi mudah diperoleh (ternak babi tergolong dalam hewan omnivora) serta kotorannya berpotensi digunakan sebagai pupuk alami (Kueain et al, 2017).…”
Section: Pendahuluanunclassified